2017
DOI: 10.1007/s00276-017-1839-6
|View full text |Cite
|
Sign up to set email alerts
|

The ethmoidal arteries: a cadaveric study based on cone beam computed tomography and endoscopic dissection

Abstract: CBCT was adequate in identifying and localizing EAs. In addition, it can be used to exclude the presence of MEA and dehiscence of ethmoidal canals, whereas the accuracy in detecting these anatomic variants was low.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
16
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 29 publications
4
16
2
1
Order By: Relevance
“… 8 , 11 A recent study on cone beam CT reported that the MEA was identified in 28.6% of nasal cavities. 20 When present, its mean distance from the skull base was 1.0 mm, which was close to that of the PEA (1.2 mm). Unlike the PEA, an extremely long distance from the skull base was not observed with the MEA ( Figures 3(b) and 4(a) ).…”
Section: Discussionsupporting
confidence: 66%
“… 8 , 11 A recent study on cone beam CT reported that the MEA was identified in 28.6% of nasal cavities. 20 When present, its mean distance from the skull base was 1.0 mm, which was close to that of the PEA (1.2 mm). Unlike the PEA, an extremely long distance from the skull base was not observed with the MEA ( Figures 3(b) and 4(a) ).…”
Section: Discussionsupporting
confidence: 66%
“…Moon et al 12 reported that the AEC was located between the second and the third lamella in 87.1% of cases and within the second and the third lamella in 12.9% of cases. Contrary to these reports, Ferrari et al 4 reported that the AEC was located within the second lamella in 3.6% of cases, between the second and the third lamella in 32.1% of cases, and within the third lamella in 64% of cases. Therefore, the anatomic variations of the AEA are wide, and it is essential to be aware of these variants in the surgical field.…”
Section: Introductionmentioning
confidence: 80%
“…Our results showed that there was poor interobserver agreement in the assessment of the dehiscence of the AEC on CT. To the best of our knowledge, the interobserver agreement on assessment of AEC dehiscence on CT has not been previously published. Evaluation of the interobserver agreement has been previously performed in the identification of the AEC on coronal planes 17 and in the assessment of the anatomic landmarks of the AEA on coronal CT. 18 The accuracy of CT in identifying AEC dehiscence has been previously estimated by Ferrari et al, 4 who described poor accuracy of cone-beam CT (slice thickness 2.0-2.5 mm) due to inadequate spatial resolution, making anatomical dissection the best modality to assess this feature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The great discrepancy between the expected and observed (29%) incidence of alveolar anesthesia after type D EMM prompted us to analyze the neural anastomotic network around the ASAN (ASAN‐NAN). In view of its excellent spatial resolution, cone‐beam computed tomography (CBCT) was used to study the course of the superior alveolar nerve. Furthermore, modular extensions of type D EMM were designed in a preclinical setting with the intent to limit injury to the ASAN‐NAN.…”
Section: Classification Of Emms Published By Our Groupmentioning
confidence: 99%